Intrahepatic fat and postprandial glycaemia increase after consumption of a diet enriched in saturated fat compared to free sugars - Parry, S; Mozes, D; Cornfield, T; Hutchinson, M; Piche, M-E; Hülsmeier, A; Hornemann, T; Dyson, P; Hodson, L (American Diabetes Association, 2020)
Objective: Debate continues regarding the influence of dietary fats and sugars on the risk of developing metabolic diseases, including insulin resistance and nonalcoholic fatty liver disease (NAFLD). We investigated the effect of two eucaloric diets, one enriched with saturated fat (SFA), the other enriched with free sugars (SUGAR), on intrahepatic triacylglycerol (IHTAG) content, hepatic de novo lipogenesis (DNL) and whole-body postprandial metabolism in overweight males.